Food becoming compost: encountering and negotiating disgust in household sustainability. Issue 3 (2nd July 2020) - Ames, Elloise; Cook, Nicole
ABSTRACT: Human encounters with waste can trigger reflections on taken-for-granted assumptions about consumption. Taking this observation as its starting point, this paper explores whether and how the introduction of the kitchen caddy and food waste composting at the municipal scale generates new environmental subjectivities in Australian homes. Using visceral research methods, the paper shows that, other than participation in municipal composting, close encounters with food becoming compost do not trigger more experimental or sustainable relationships with food. Rather, they trigger new configurations of cleanliness, tidiness and storage as participants seek to stabilise their home against the disruptive sight, smell and touch of food becoming compost. In unsettling the boundaries between humans and nonhumans, and cleanliness and chaos, food becoming compost produces visceral disgust among residents who are primed through modern home cultures to maintain cleanliness, control and the prevention of nonhuman intrusions at home. The success of municipal composting thus hinges on households' commitment to 'sustainability work' in placing, storing, cleaning and sealing food to reconfigure the modern home for waste recovery. Reconceptualising municipal composting as a co-production of sensory engagement and household practices, we centre a visceral politics of household sustainability at the heart of municipal composting and resource management.